2018
DOI: 10.1016/j.nicl.2017.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Hypersynchrony in MEG spectral amplitude in prospectively-identified 6-month-old infants prenatally exposed to alcohol

Abstract: Early identification of children who experience developmental delays due to prenatal alcohol exposure (PAE) remains a challenge for individuals who do not exhibit facial dysmorphia. It is well-established that children with PAE may still exhibit the cognitive and behavioral difficulties, and individuals without facial dysmorphia make up the majority of individuals affected by PAE. This study employed a prospective cohort design to capture alcohol consumption patterns during pregnancy and then followed the infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…In other studies, infants with high prenatal exposure to alcohol have been shown to demonstrate hypersynchrony, resulting in significantly higher power in a wide range of frequencies (Chernick, Childiaeva, & Ioffe, 1983;Havlicek, Childiaeva, & Chernick, 1977;Stephen et al, 2018), therefore the directionality of EEG power and developmental outcomes may vary based on the characteristics of the sample.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In other studies, infants with high prenatal exposure to alcohol have been shown to demonstrate hypersynchrony, resulting in significantly higher power in a wide range of frequencies (Chernick, Childiaeva, & Ioffe, 1983;Havlicek, Childiaeva, & Chernick, 1977;Stephen et al, 2018), therefore the directionality of EEG power and developmental outcomes may vary based on the characteristics of the sample.…”
Section: Discussionmentioning
confidence: 96%
“…As we excluded infants who were born before 37 weeks gestational age or admitted to the NICU at birth, this resulted in a sample of infants with potentially fewer adverse prenatal exposures, for example, alcohol, smoking, recreational drugs, and/or psychiatric medications. In other studies, infants with high prenatal exposure to alcohol have been shown to demonstrate hypersynchrony, resulting in significantly higher power in a wide range of frequencies (Chernick, Childiaeva, & Ioffe, ; Havlicek, Childiaeva, & Chernick, ; Stephen et al, ), therefore the directionality of EEG power and developmental outcomes may vary based on the characteristics of the sample.…”
Section: Discussionmentioning
confidence: 97%
“…27 The association was persistent across all frequency bands and was most prominent in left anterior and posterior temporal regions. 27 Although 1 study found no differences in EEG power in infants with PTE compared with controls with minimal or no exposure, 24 more recent data suggest neurophysiologic sensitivity to prenatal nicotine exposure (PNE). An EEG/event-related potential study examined the auditory K-complex in infants 3 to 5 months old with PNE and found reduced delta power compared with unexposed infants in non-REM sleep.…”
Section: Introductionmentioning
confidence: 94%
“…Finally, reliance on structured questionnaires involves inherent limitations of potential bias from both participants and researchers. Objective physiological measures, such as those obtained through rigorous standardized examiner‐administered evaluation or neuroimaging (Stephen et al., ), and other experimental approaches including eye movement (Zhang et al., ) and SFP (Lowe et al., ), might be more sensitive to the identification of PAE effects in young children and requires continued study through prospective cohorts.…”
Section: Discussionmentioning
confidence: 99%